Duties to Others
XVIII, 320 p.
Keywords: Despite reservoirs of moral discourse about duties in religious communities, professional caregiving traditions, and philosophical perspectives, the dominant moral language in contemporary biomedical ethics is that of `rights'. Duties to Others begins to correct this imbalance in our ethical language through theoretical expositions of the ideas of duty and of the `other', and by applied exemplifications of particular duties to identified others that arise in the context of health care. A pronounced multidisciplinary orientation informs this analysis of our moral call to respond to the needs of others. The essays in this volume offer a stimulating intellectual freshness through a continual engagement of theological, professional, and philosophical understandings of the duties that arise in our relationships with others in medicine, nursing, and social contexts. Duties to Others provides provocative challenges about the terrain of our moral world for both students and professionals in biomedical ethics, medicine, philosophy, and theology.